Performance evaluation of single stage diaphragmless vertical gas gun for nitrogen and helium gas propellants - Peter A. GARDINER (The Japan Society of Mechanical Engineers, 2016)
The main difficulty in conducting a high velocity experiment with a projectile accelerator is predicting the projectile velocity with great accuracy. This is of crucial importance in order to keep experimental conditions constant. During the design process of the single stage diaphragmless vertical gas gun installed at the Impact Engineering Laboratory in Ritsumeikan University, a theoretical formula proposed by Seigel was used to predict the projectile velocity for various ranges of gas pressure. However, the complexity of projectile dynamics such as frictional effects between the projectile and the launch tube, the aerodynamics of the projectile, temperature effects and pressure disturbances occurring during projectile acceleration are factors excluded from the theoretical formula, making it challenging to predict the actual velocity of the projectile. Hence, it was necessary to conduct a performance evaluation of single stage diaphragmless vertical gas gun. For the experiment, flat projectiles were used consisting of a brass impactor and a high-density polyethylene sabot. A neodymium magnet was placed inside the sabot for velocity measurement using Magnet-Coil method, and nitrogen and helium were selected as gas propellants. The experimental results were carefully analyzed, and found to show a similar trend with the theoretical solution. Fitting parameters were then introduced to make the final adjustment to the theoretical formula, showing good agreement with the experimental results.